Study of the Electrophysical Properties of Composite Varistors Based on Zinc Oxide and Polymer (Polyaniline) - Sajedeh Mohammadi Aref; Hassan Bidadi; Shamestan Hasanli (International Journal of Polymer Science)
In this experimental work, current-voltage characteristics of composite varisrors prepared on the base of zinc oxide with different weight percentages of polyaniline and temperature dependence of the samples characteristics have been studied. The activation energy of donor levels as well as the existence of hysteresis loop has been investigated. The comparison of experimental results shows that by increasing the polymer percentage in the varistor structure as long as the nonlinear behavior is conserved, the threshold voltage increases. This comparison also indicates that increasing the polymer content in the varistor structure causes the temperature dependence of threshold voltage to decrease. It is also concluded that, by the increase of polymer content in the varistor structure, the activation energy of donor levels and the hysteresis value are increased.